Agreements conferring jurisdiction in favour of a foreign court included in a bill of lading: costums and contractual freedom in the maritime sector. Commentary on the order of 5 July 2019 of the AAP de Madrid (Section 28) - Magallón Elósegui, Nerea (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
Jurisdiction agreements in favour of a foreign court included in a bill of lading have traditionally been used in the maritime sector as a mechanism that streamlines commercial practice while seeking a balance between the parties that will resolve their disputes in a neutral and specialized forum. However, the presence of these clauses in standardized contracts encourages discussion about the existence of a weak party in the relationship and the imposition of the clause without its consent and to the detriment of its interests. In this decision both positions are glimpsed reflecting a dichotomy that has resurfaced as a result of the new Law of Maritime Navigation which, with the aim of avoiding the abuses inherent in the submission clauses suffered by third parties possessing bills of lading, incorporates strict requirements that alter the line followed by the European regulations.